Antarctic Bottom Water production from the Vincennes Bay Polynya, East Antarctica. Issue 10 (29th May 2014) - Kitade, Yujiro; Shimada, Keishi; Tamura, Takeshi; Williams, Guy D.; Aoki, Shigeru; Fukamachi, Yasushi; Roquet, Fabien; Hindell, Mark; Ushio, Shuki; Ohshima, Kay I.
Abstract One year moorings at depths greater than 3000 m on the continental slope off Vincennes Bay, East Antarctica, reveal the cold (<−0.5°C) and fresh (<34.64) signals of newly formed Antarctic Bottom Water (AABW). The signal appeared in June, 3 months after the onset of active sea‐ice production in the nearby Vincennes Bay Polynya (VBP). The AABW signal continued for about 5 months at two moorings, with 1 month delay at the western site further downstream. Ship‐based hydrographic data are in agreement, detecting the westward spread of new AABW over the continental slope from VBP. On the continental shelf, Dense Shelf Water (DSW) formation is observed by instrumented seals, in and around the VBP during autumn, and we estimate its transport to be 0.16 ± 0.07 (× 106m3s−1). We conclude that the DSW formed in this region, albeit from a modest amount of sea‐ice production, nonetheless contributes to the upper layer of AABW in Australian‐Antarctic Basin.